Adsorption of ciprofloxacin pollutants in aqueous solution using modified waste grapefruit peel. Issue 2 (17th January 2021) - Fu, Yanzhen; Yang, Zili; Xia, Yangchao; Xing, Yaowen; Gui, Xiahui
ABSTRACT: The feasibility of using discarded solid biomass as modified waste grapefruit peel (MWGP) for the removal of ciprofloxacin (CIP) pollutants from aqueous solution was explored in terms of equilibrium studies, kinetic studies, and adsorption mechanism elucidation. Characterization of MWGP by SEM and FTIR analyses indicate irregular pore structures and carboxylates as the active adsorption sites. Optimum adsorption conditions were determined in terms of pH, Na + /Ca 2+ concentration, adsorbent time, adsorbent dosage, and initial concentration of CIP. Maximum uptake of CIP is 1.71 mmol·g −1 under optimal experimental conditions. Adsorption data fit the Langmuir isotherm model and the adsorption process follows pseudo-second order kinetics. Mechanistic studies showed that electrostatic, hydrophobic, hydrogen bonding, and π-π interactions are the main driving forces for CIP adsorption on MWGP. These findings suggest that MWGP is a promising adsorbent for the removal of CIP from aqueous solutions.